Partnership to Create a Food Independent Urban Village in Tanjung Mas, Semarang City - Irsadi, Andin; Partaya, Partaya; Jabbar, Abdul (Jurnal Abdimas, 2024)
Tanjung Mas Village, North Semarang District is one of the areas in Semarang City that is vulnerable to food insecurity. This food insecurity is caused by the high level of poverty in this region. Poverty has a big impact on food security because poor people are unable to provide sufficient amounts of food, either by producing it themselves or by buying it. This condition encourages the government and society to start trying to fulfill their food needs independently through farming. However, these efforts are hampered by limited agricultural land availability. The aim of the community service program is to provide knowledge, skills and facilitate urban farming facilities to achieve food independence in the Tanjung Mas, Semarang City. The methods used are socialization, counseling, dissemination, training and facilitation of urban farming facilities. The results of this community service program are that the community has an understanding of urban farming, knows the technologies in urban farming, has verticulture skills, and verticulture facilities are available as learning demonstration plots.